Determination of physiological data from a mathematical analysis of the running performance of elite female athletes - Ward-Smith, A. J.; Mobey, A. C. (Journal of Sports Sciences, 1995)
A method of analysis developed and applied to male athletes is used to determine physiological data for female athletes. The analytical method rests on the construction of an energy balance incorporating a mathematical representation of each of the major terms in the balance. By recasting the energy balance, a relationship between race distance and running time is derived. Excellent agreement with results for female athletes from recent Olympic Games for distances from 100 to 10,000 m is established. From the analysis, representative values of the maximum anaerobic power, the maximum aerobic power and the rate of degradation of mechanical energy into heat are derived for elite female athletes.